Violence and New Religious Movements: The Relationship Between Cognitive Dissonance and Perceived Pressure - Connah, Leoni (International journal for the study of new religions, 2020)
This article revisits the controversies sparked by two new religious movements (NRMs) in the run up to the millennium—the tragedies that unfolded in Jonestown and Tokyo—which have forever altered discussions on new religions and violence. This paper explores the impact of pressures both external and internal on The Peoples Temple and Aum Shinrikyo and suggests two new points of focus: perceived pressure and cognitive dissonance. As time progressed, both movements experienced rejection from wider society, leading them to become increasingly world-rejecting (Wallis 1984) and causing dissonance between the teachings of their prophetic leaders and their uncomfortable reality. Actual exter nal pressures such as persecution by social and governmental agencies, as well as the perception of external pressure (the feeling of rejection), strengthened the internal pressures of cognitive dissonance and ultimately to self-destructive violence in such groups. For decades scholars have investigated the impacts of endogenous and exogenous pressures on NRMs, and while this article focuses on events that occurred over twenty years ago, there is still room to explore the dynamic relationship between the perception of pressure and catastrophic violence.